Efektivitas Pelatihan Regulasi Diri untuk Menurunkan Prokrastinasi Mahasiswa dalam Mengerjakan Skripsi - Hariz Enggar Wijaya; Fuad Nashori (JIP (Jurnal Intervensi Psikologi), 2015)
Research on procrastination has been widely done, however, there was limited research using interventions. Based on the concept of self-regulated learning, the effectiveness of self-regulation training was examined to reduce student procrastination on thesis writing. The hypothesis was the self-regulation training will reduce the procrastination level of undergraduate thesis writing. Ten psychology students participated in this training and measured by TKSS of Djing (2010). This study used a quasi-experimental with one-group pretest-posttest design. Result showed that self-regulation training effectively reduce student procrastination on thesis writing, t (5) = 2,132, p = 0, 04 (one-tailed), (p < 0.05) and D = 0, 69. Therefore, self-regulation training could be taken to overcome student procrastination on thesis writing. It can be done as a preventive or curative tool.Keywords: self-regulation training, procrastination, students